The Injustice of Criminal Guidelines in the Act of Corruption Crime - Margono, Margono; Bawono, Bambang Tri; Prayitno, Ahmad Hadi; Rimbawan, Andhika Yuli; Laksana, Andri Winjaya (Jurnal Hukum, 2024)
Corruption is an extraordinary crime that can damage the joints of the life of the nation and state. Corruption can cause various negative impacts, such as: reducing state revenues from the tax sector, reducing government spending in the education sector, resulting in low-quality infrastructure being built, slowing economic growth, causing government instability. The aims of this study is to find out about the injustice in the regulation of criminal guidelines for corruption crimes which makes the enforcement of corruption laws less strict in their punishment. The research method used normative juridical. The results of the study state that the Criminal Guidelines for Articles 2 and 3 of the Corruption Eradication Law in order to better cover other articles of corruption crimes and must change the criminal guidelines for very large losses must consider implementing maximum punishment in accordance with the criminal guidelines, the novelty produced for the criminal guidelines for corruption crimes must be regulated regarding the highest loss value must be adjusted to the heaviest punishment in accordance with the criminal guidelines in the Criminal Code.